2020
DOI: 10.1186/s12931-020-1290-9
|View full text |Cite
|
Sign up to set email alerts
|

“Can do, don’t do” are not the lazy ones: a longitudinal study on physical functioning in patients with COPD

Abstract: Background and objective: Reduced physical capacity (PC) and physical activity (PA) are common in COPD patients and associated with poor outcome. However, they represent different aspects of physical functioning and interventions do not affect them in the same manner. To address this, a new PC-PA quadrant concept was recently generated to identify clinical characteristics of subgroups of physical functioning. The objective of this study was to I) proof the new concept and to verify their differentiating clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
3
14
4
Order By: Relevance
“…Despite applying the same operationalization to calculate relative PC, our study included more participants (60.5%) in the “can do” categories (Quadrants 2 and 4) than the original study (45%) [ 7 ]. Accordingly, the average number of daily steps found in the present study (5.850) was slightly higher than in the two other quadrant studies (4.421 [ 12 ] vs. 5.521 [ 7 ]) and in most other COPD studies with an objective PA assessment (4.579) [ 47 ]. Notably, we identified these values and quadrant distributions despite the fact that the research took place in the setting of inpatient rehabilitation and that the individuals of the present sample exhibited more severely impaired lung function (FEV 1 %pred: 40) than the individuals in the other quadrant studies coming from usual outpatient care (FEV 1 %pred: 44 [ 12 ] vs. 56 [ 7 ]).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Despite applying the same operationalization to calculate relative PC, our study included more participants (60.5%) in the “can do” categories (Quadrants 2 and 4) than the original study (45%) [ 7 ]. Accordingly, the average number of daily steps found in the present study (5.850) was slightly higher than in the two other quadrant studies (4.421 [ 12 ] vs. 5.521 [ 7 ]) and in most other COPD studies with an objective PA assessment (4.579) [ 47 ]. Notably, we identified these values and quadrant distributions despite the fact that the research took place in the setting of inpatient rehabilitation and that the individuals of the present sample exhibited more severely impaired lung function (FEV 1 %pred: 40) than the individuals in the other quadrant studies coming from usual outpatient care (FEV 1 %pred: 44 [ 12 ] vs. 56 [ 7 ]).…”
Section: Discussioncontrasting
confidence: 78%
“…Accordingly, the average number of daily steps found in the present study (5.850) was slightly higher than in the two other quadrant studies (4.421 [ 12 ] vs. 5.521 [ 7 ]) and in most other COPD studies with an objective PA assessment (4.579) [ 47 ]. Notably, we identified these values and quadrant distributions despite the fact that the research took place in the setting of inpatient rehabilitation and that the individuals of the present sample exhibited more severely impaired lung function (FEV 1 %pred: 40) than the individuals in the other quadrant studies coming from usual outpatient care (FEV 1 %pred: 44 [ 12 ] vs. 56 [ 7 ]). However, a considerable portion of participants were still involved in working life (76.6%); hence, the sample was significantly younger (mean age: 58 years) than those in other studies using the concept (mean age: 63 years [ 12 ] and 63 years [ 7 ]).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Likewise, Bradley et al [ 21 ] reported that neither lung function (FEV 1 % predicted) nor disease severity (BSI score) was correlated with sedentary behaviour in patients with bronchiectasis. Data collected from patients with COPD have shown that physical activity decliners vary from 35% to 59% over time [ 41 , 42 ], but the clinical characteristics could not predict or explain the subsequent patterns of decline, included the number of exacerbations [ 42 , 43 , 44 , 45 ]. This indicates that the common clinical and functional assessments are unsuitable for use as indicators of risk of physical activity decline and/or increase in sedentary behaviour, which further highlights the need for further longitudinal and objective assessment in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research identified inactive, active improvers and active decliners as 3 distinct patterns on patients with COPD physical activity natural progression over 1-year 49 . Not only efficiently targeted intervention on PADL is needed to promote long sustainable healthy habits, as there is growing evidence that its systematic assessment might be more sensitive detecting progressive disease deterioration 50 . Because of this, we recommend a comprehensive regular assessment with oximetry and accelerometery, as it provides combined perspectives about PADL: quantity (duration), intensity (METs), modality (type) and quality (SpO 2 and HR).…”
Section: Discussionmentioning
confidence: 99%